The Immunostimulatory Effects of Commercial Feed Additives on Growth Performance, Non-specific Immune Response, Antioxidants Assay, and Intestinal Morphometry of Nile tilapia, Oreochromis niloticus - Kord, Mohamed Ibrahim; Srour, Tarek Mohamed; Omar, Eglal Ali; Farag, Ahmed Awny; Nour, Abdel Aziz Moussa; Khalil, Hala Saber (Frontiers in Physiology, 2021)
The main objective of the present research was to investigate the impacts of commercial immunostimulants on growth, non-specific immune response, antioxidant enzymes, and intestinal morphometry of Nile tilapia, Oreochromis niloticus. Fish (100 ± 6.5 g) were randomly divided into five groups in triplicates (150 fish in each replicate), stocked in 20 m2 of aerated concrete ponds. The fish were fed on a control diet (30.0 % crude protein) (control), and four experimental diets supplemented with Yeast Plus®, Digestarom®, and Biotronic® Top3 at 1 kg tonne-1, and Sanolife PRO-F® at 0.5 kg tonne-1. After the experimental period, the highest significant yield (kg m-3), mean final weight (g fish-1), average weight gain (g fish-1), and specific growth rate (% body weight day-1), were recorded in fish fed on the diet supplemented by Sanolife PRO-F, followed by Yeast Plus ponds. The lowest yield was recorded in the control group. However, the feed conversion ratio was significantly decreased with Sanolife PRO-F diet. Furthermore, the haematological analysis increased in the following ascending order: Sanolife PRO-F®; Yeast Plus®; Biotronic Top3® and finally Digestarom® groups. The lowest concentrations of white blood cells, red blood cells, hematocrite, and hemoglobin (P≤0.05) were observed in the control group. The levels of phagocytic activity and phagocytic index were significantly higher in fish fed with Sanolife PRO-F® group (P ≤ 0.05). Likewise, serum lysozyme activity was significantly highest in Sanolife PRO-F (0.63 and 0.68 U/mL, after 0.5 min and 3 min respectively). Levels of total serum proteins, globulin, Immunoglobulin M, catalase, and sodium dismutase were significantly higher in fish fed with Sanolife PRO-F® supplement. On the contrary, length measurement of the intestinal villus height/width, absorption area, crypt depth, and goblet cells, were significantly lower in the control group, whereas their highest values was observed in fish fed Sanolife PRO-F (P ≤ 0.05). Consequently, Sanolife PRO-F® is recommended at a level of 0.5 kg tonne-1, to improve the growth performance, antioxidative capacity, and immune response of Nile tilapia.